2018
DOI: 10.1093/logcom/exy024
|View full text |Cite
|
Sign up to set email alerts
|

Judgment aggregation in dynamic logic of propositional assignments

Abstract: Judgment aggregation models a group of agents having to collectively decide over a number of logically interconnected issues starting from their individual opinions. In recent years, a growing literature has focused on the design of logical systems for social choice theory, and for judgment aggregation in particular, making use of logical languages designed ad hoc for this purpose. In this paper we deploy the existing formalism of Dynamic Logic of Propositional Assignments (DL-PA), an instance of Propositional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Dynamic Logic of Propositional Assignments DL-PA [BHT13,BHST14] is a version of Propositional Dynamic Logic PDL whose atomic programs are assignments of propositional variables p to true or false, respectively written +p and −p. We and coauthors have shown that many knowledge representation concepts and formalisms can be captured in DL-PA, such as update and revision operations [Her14], database base fusion and repair operations [FHR19], planning [HMNDBW14,HMV19], lightweight dynamic epistemic logics [CS15,CHM + 16,CS17], and judgment aggregation [NGH18]. The mathematical properties of DL-PA are simpler than those of PDL, in particular, the Kleene star can be eliminated [BHT13] and satisfiability and model checking are both PSPACE complete [BHST14].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic Logic of Propositional Assignments DL-PA [BHT13,BHST14] is a version of Propositional Dynamic Logic PDL whose atomic programs are assignments of propositional variables p to true or false, respectively written +p and −p. We and coauthors have shown that many knowledge representation concepts and formalisms can be captured in DL-PA, such as update and revision operations [Her14], database base fusion and repair operations [FHR19], planning [HMNDBW14,HMV19], lightweight dynamic epistemic logics [CS15,CHM + 16,CS17], and judgment aggregation [NGH18]. The mathematical properties of DL-PA are simpler than those of PDL, in particular, the Kleene star can be eliminated [BHT13] and satisfiability and model checking are both PSPACE complete [BHST14].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic Logic of Propositional Assignments DL-PA [BHT13,BHST14] is a version of Propositional Dynamic Logic (PDL) whose atomic programs are assignments of propositional variables p to true or false, respectively written +p and −p. We and coauthors have shown that many knowledge representation concepts and formalisms can be captured in DL-PA, such as update and revision operations [Her14], database repair [FHR19], lightweight dynamic epistemic logics [CS15,CHM + 16,CS17], planning [HMNDBW14], and judgment aggregation [NGH18]. The mathematical properties of DL-PA are simpler than those of PDL, in particular, the Kleene star can be eliminated [BHT13] and satisfiability and model checking are both PSPACE complete [BHST14].…”
Section: Introductionmentioning
confidence: 99%